PERBANDINGAN UNDANG-UNDANG NOMOR 3 TAHUN 1997 TENTANG PENGADILAN ANAK DENGAN UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK DALAM PEMERIKSAAN PERKARA ANAK DI PENGADILAN ANAK - armanila febri; Gusliana H.B.; Davit Ramadhan (Fiat Justisia: Jurnal Ilmu Hukum, 2014)
Children are people who have physical or mental limitations. Limitation understand everything, tends to bring negative influences into themselves and can cause it to do damage (juvenile delinquency) or even become perpetrators of delinquency (a criminal offense). Law No. 3 of 1997 on Juvenile Justice (Juvenile Court Act), in principle, was born to protect and nurture children in conflict with the law (ABH). However, it was legally incapable angle Court Law provide legal protection against the ABH. Thus was born the amount of number 11 of 2012 on the Criminal Justice System Child (Law SPPA) to replace the Juvenile Justice Act. In the case of change of the Act there are striking differences in issues related to children in the examination of the case law SPPA. The purpose of this paper are: first, to determine the child's examination of the case in court demanding the setting ABH Court Law Act with SPPA angle. Second, to determine the advantages and disadvantages of the examination of cases in court, according to Law ABH juvenile justice law with Law SPPA. Keywords: Comparative, investigation, Case, Children in conflict with the law(ABH), Juvenile Justice